Coastal Communities' Willingness to Pay for Mangrove Ecotourism at Marudu Bay, Sabah, Malaysia - Fazilah Musa; Norashikeen Mohd Fozi; Diana Demiyah Mohd Hamdan (Penerbit UMT, 2020)
The revenue contribution of mangrove forests to Malaysia’s economic growth is usually associated with fishing. Generally, fishing is one of the main sources of income for coastal communities, and mangroves are found in abundance in coastal areas. Nowadays, mangrove forests have become a very significant product in the tourism sector. It enhances Malaysia’s economy through increasing the earnings of local communities and creating more job opportunities. The potential of mangrove forests as a dynamic ecotourism industry is being rapidly capitalized in many parts of Malaysia. However, the economic benefits of mangrove forests in the tourism sector have not been used to its fullest because of the non-existent market for this resource. This study aims to determine the willingness to pay (WTP) of the coastal communities in Marudu Bay, Sabah, to develop their mangrove areas as an ecotourism destination. To achieve this, the study engages in the contingent valuation method (CVM). Questionnaires were distributed to 400 respondents from five selected coastal villages, asking them whether they are willing to pay for five bid prices, RM5, RM10, RM15, RM20 or RM30, for mangrove ecotourism conservation. Logistic regression was applied to estimate the mean WTP by using three different types of logit models. Results indicate that the estimated mean for each WTP model is as follows: Model 1 (the full model) at RM12.96/person/year, Model 2 (the restricted model) at RM16.08/ person/year and Model 3 at RM25.68/person/year, respectively. The coastal communities’ responses of their WTP were based on the bidding prices and their socio-demographic variables. The majority of them had the WTP because they were confident that the conservation of mangroves promotes sustainable ecotourism and can improve community income, hence would better their livelihoods for generations to come.